Paleogeographic and sedimentary evolution of the South Pyrenean foreland basin. (March 2020) - Garcés, Miguel; López-Blanco, Miguel; Valero, Luis; Beamud, Elisabet; Muñoz, Josep Anton; Oliva-Urcia, Belén; Vinyoles, Andreu; Arbués, Pau; Cabello, Patricia; Cabrera, Lluís
Abstract: During the Paleogene and Neogene the NE Iberian plate underwent significant paleogeographic changes driven by the Iberian and European plate collision and the resulting formation of the Pyrenean orogen and its corresponding foreland basin. Shortening resulted in the advance of the orogenic wedge, emplacement of allochthonous units, and progressive basin partitioning. Sediment transfer systems reacted to the evolving paleogeographic scenario, shifting from forebulge to foredeep and wedge-top settings. Critical reorganizations included successive shifts from open to close drainage conditions, which had an strong impact on accommodation, and the stratigraphic architecture of the basin infill, overfill and later erosion. The aim of this work is to synthesize the paleogeographic and sedimentary evolution of the south-pyrenean foreland, with emphasis on the reconstruction of sediment routing, the evaluation of sedimentation rate trends, the timing of sedimentary shifts and the analysis of their causes. Stratigraphic data are compiled in a comprehensive magnetostratigraphy-based chronostratigraphic framework. Besides, sedimentary and structural data are put together to produce a series of palinspastically restored paleogeographic maps, which reflect five key stages in the evolution of the region. These stages include: 1) the Late Cretaceous tectonic inversion of the extended Iberian margin; 2) the Early Eocene formation of the southern Pyrenean foredeep; 3) the Middle Eocene widening and overfilling; 4) the late Eocene shift into an internal drainage; and 5) the Late Miocene drainage opening and erosion. In the light of these results, the variable role of tectonics, climate and eustacy at different time scales are discussed. Highlights: A paleogeographic evolution of the south pyrenean foreland from palinspastic reconstructions and a revised chronostratigraphy. Tectonics controlled the long-term processes of basin partitioning and the evolution of sediment routing systeand sinks. Climate forcing overprinted the long-term tectonic signal, pacing sedimentary sequences in the 10 5 -10 6 yr time range.